Analisis Kebijakan Pemanfaatan Hutan Konservasi untuk Wisata Alam Berbasis Asas Manfaat dan Lestari (Studi Kasus TAHURA Mangkunagoro I Karanganyar) - Muhammad Restu Putra Pratama; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the policy regarding the utilization of conservation forest areas in the Grand Forest Park (Tahura) K.G.P.A.A. Mangkunagoro I Karanganyar, particularly in the context of developing nature-based tourism grounded in the principles of benefit and sustainability. The background of this research lies in the urgency of managing conservation areas not only to preserve the environment but also to contribute to the sustainable social and economic development of surrounding communities. This research employs normative legal research methods with statutory and conceptual approaches. Data were obtained through literature study, document analysis, and direct field observation. The data analysis was conducted deductively by linking normative legal provisions with the principles of benefit and sustainability. The results indicate that the management policy of Tahura K.G.P.A.A. Mangkunagoro I has accommodated the fundamental principles of conservation as stipulated in the applicable legislation, particularly Regional Regulation of Central Java Province Number 3 of 2011. However, in practice, several potential inconsistencies remain. Therefore, it is necessary to improve the implementing regulations, technical governance, and supervision systems to ensure that the policy implementation genuinely reflects the substantive and equitable application of the principles of benefit and sustainability